Experimental Investigation on Mechanical Properties of Burnished Aluminum Metal Matrix Composites - T. Naveen Kumar, Sd. Abdul Kalam, V. S. N. Venkata Ramana, K. Sri Ram Vikas (International Journal of Advanced Science and Technology, 2020)
Aluminum metal matrix composites have been heralded as the development in advanced engineering materials. Aluminum metal matrix composites (AMMC) refer to the class of light weight, high performance material system. AA6063 applications such as window frames, door frames, roofs, and sign frames. FeTiO3 Particles were incorporated in to the matrix material in 0,5,10,15 % volume fractions by using the stir casting method. The proposed work is going to reveal effects of various burnishing parameters like burnishing speed, type of lubricants and number of passes against the considered output responses such as Surface roughness, Density, Microstructure, Tensile Strength, Fractography, Hardness, Electrical conductivity. The addition ofFeTiO3 particulates mixed with 15wt% provides consistent Surface roughness, Electrical conductivityand Hardness values improved in Burnishing.AA6063 MMC in Further addition ofFeTiO3 particulates leads to poor results reason is up to 15%wt does not mix The AA6063.